Individual Optimal Frequency in Whole-Body Vibration: Effect of Protocol, Joint Angle, and Fatiguing Exercise. Issue 12 (December 2016) - Carlucci, Flaminia; Felici, Francesco; Piccinini, Alberto; Haxhi, Jonida; Sacchetti, Massimo
Abstract : Abstract: Carlucci, F, Felici, F, Piccinini, A, Haxhi, J, and Sacchetti, M. Individual optimal frequency in whole-body vibration: effect of protocol, joint angle, and fatiguing exercise. J Strength Cond Res 30(12): 3503–3511, 2016—Recent studies have shown the importance of individualizing the vibration intervention to produce greater effects on the neuromuscular system in less time. The purpose of this study was to assess the individual optimal vibration frequency (OVF) corresponding to the highest muscle activation (RMSmax ) during vibration at different frequencies, comparing different protocols. Twenty-nine university students underwent 3 continuous (C) and 2 random (R) different vibrating protocols, maintaining a squat position on a vibration platform. The C protocol lasted 50 seconds and involved the succession of ascending frequencies from 20 to 55 Hz, every 5 seconds. The same protocol was performed twice, having the knee angle at 120° (C) and 90° (C90), to assess the effect of joint angle and after a fatiguing squatting exercise (CF) to evaluate the influence of fatigue on OVF assessment. In the random protocols, vibration time was 20 seconds with a 2-minute (R2) and a 4-minute (R4) pauses between tested frequencies. Muscle activation and OVF values did not differ significantly in the C, R2, and R4 protocols. RMSmax was higher in C90 ( p < 0.001) and in CF ( p = 0.04) compared with the C protocol. Joint angle and fatiguing exercise had no effect on OVF. In conclusion, the shorter C protocol produced similar myoelectrical activity in the R2 and the R4 protocols, and therefore, it could be equally valid in identifying the OVF with considerable time efficiency. Knee joint angle and fatiguing exercise had an effect on surface electromyography response during vibration but did not affect OVF identification significantly.